Who's your daddy? Intergenerational mobility in the U.S. financial industry - Henrik Schürmann (University of Wuppertal, Schumpeter School of Business and Economics, 2020)
This paper investigates the intergenerational mobility with regard to people's decision to work in the U.S. financial industry over the last 47 years. I present evidence that children of fathers who worked in the financial industry during their childhood are about 8 percentage points more likely to work in finance themselves. This increase in likelihood is greater than in most other industries and is driven solely by wealthier families. In addition, I document that second-generation finance industry employees whose fathers already worked in finance enjoy a substantial income surplus compared to their industry peers.
urn:nbn:de:hbz:468-20200817-104413-7
Keywords: G20; J24; J30; J62; L14; 330; Financial industry; Intergenerational mobility; Informal networks; Nepotism